BITE : Recipes for Remarkable Research. - Williams, Alison; Jones, Derek; Robertson, Judy (Brill / Sense [Imprint] BRILL., 2014)
FREELY AVAILABLE ONLINE AS OPEN ACCESS BOOK! BITE: Recipes for remarkable research is an edited field book capturing the research, learning and experiences of an international network of scholars studying effective and creative research environments. The book encapsulates what it is that enables remarkable research, and offers, as Professor Lizbeth Goodman says, "practical, evidence-based instantiations of ideas and innovations" as well as theoretical knowledge. It is set out as a recipe book, with supporting academic papers and case studies. The recipes present research and advice from a wide range of subject areas in an instantly recognisable format. Each recipe enables the reader to take practical steps to understand and develop their own research at all levels, from personal solo work and group collaborations, to an institutional and architectural dimension. Whether you are a PhD student, early career researcher, professor or decision-maker, these recipes, case studies and papers invite you to consider research habits, approaches and environments in interesting and different ways.